The chemistry book : from gunpowder to graphene, 250 milestones in the history of chemistry - Lowe, Derek B. (Sterling, 2016)
Presents 250 milestones in the world of chemistry from the formation of crystals (c. 500,000 BCE) to the image of single-molecules (2013 ADE) as well as a couple forward-looking milestones.